Understanding the management of heart failure with preserved ejection fraction: a qualitative multiperspective study - Sowden, E; Hossain, M; Chew-Graham, C; Blakeman, T; Tierney, S; Wellwood, I; Rosa, F; Deaton, C (Royal College of General Practitioners, 2020)
Background About half of all people with heart failure have heart failure with preserved ejection fraction (HFpEF), in which the heart is stiff. This type of heart failure is more common in older people with a history of hypertension, obesity, and diabetes mellitus. Patients with HFpEF are often managed in primary care, sometimes in collaboration with specialists. Knowledge about how best to manage this growing population is limited, and there is a pressing need to improve care for these patients.